Using ontologies to describe mouse phenotypes. - Georgios V. Gkoutos; Eain C.J. Green; Ann‐Marie Mallon; John M. Hancock; Duncan Davidson (2004)
Abstract The mouse is an important model of human genetic disease. Describing phenotypes of mutant mice in a standard, structured manner that will facilitate data mining is a major challenge for bioinformatics. Here we describe a novel, compositional approach to this problem which combines core ontologies from a variety of sources. This produces a framework with greater flexibility, power and economy than previous approaches. We discuss some of the issues this approach raises.